Strategi Guru Bahasa Bali Dalam Memberikan Pembelajaran Peparikan Kepada Siswa Kelas VIII SMP Negeri 1 Marga - I Putu Deva Mahendra Adiputra; Gusti Nyoman Mastini; I Wayan Artayasa (Metta : Jurnal Ilmu Multidisiplin, 2026)
Balinese language learning in schools plays an essential role in preserving local language and strengthening Balinese cultural identity amid modern social changes. One learning material that requires special attention is peparikan, because it demands vocabulary mastery, language sensitivity, creativity, and students’ ability to arrange meaningful expressions according to Balinese literary rules. This study aims to describe the obstacles encountered in teaching peparikan to eighth-grade students of SMP Negeri 1 Marga, Marga District, Tabanan Regency, in the 2025/2026 academic year, and to explain the strategies applied by teachers to overcome these obstacles. This research employed a qualitative approach supported by Piaget’s constructivist theory, behaviorist theory, and Herzberg’s motivation theory. The data were collected from primary and secondary sources through observation, interviews, documentation, and literature study. The collected data were then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings reveal that the obstacles in peparikan learning consist of teacher-related and student-related challenges. The teacher-related obstacles include students’ limited ability to use Balinese properly, their dependence on examples, and differences in students’ learning abilities. Meanwhile, student-related obstacles include difficulty in selecting appropriate diction and hesitation to ask questions when they do not understand the material. To address these problems, the teacher provided appreciation for students’ efforts, used relevant learning media, created opportunities for asking questions, and implemented Problem Based Learning to encourage active participation. This study concludes that successful peparikan learning depends on the teacher’s ability to build a communicative classroom atmosphere, provide gradual examples, and encourage students’ confidence in using Balinese creatively.